2003
DOI: 10.1007/s11920-003-0073-6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and neuropsychiatric aspects of subclinical hypothyroidism: Significance in the elderly

Abstract: The effects of overt hypothyroidism (HO) on cognition and mood are well established, and HO is considered a common cause of reversible dementia. There is now increasing evidence to suggest that subclinical hypothyroidism (ie, elevated thyroid stimulating hormone in the presence of normal thyroxine concentrations) may be a predisposing factor for depression, cognitive impairment, and dementia. Subclinical hypothyroidism is more common than HO and is most prevalent in the elderly, particularly in women. Older ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 46 publications
2
51
0
8
Order By: Relevance
“…Indeed, it has been shown in animals that retinoid, as well as thyroid, status modulates the plasticity of the adult brain (24,71) and that their age-associated alteration induces cognitive impairment (72). Moreover, high serum TSH level has been associated with depression in the elderly (73) and hypothyroidism is well known to induce cognitive impairment and dementia (74,75). The role of retinoids in brain aging seems of primary importance itself, in that evidence for defective retinoid transport and function in late-onset Alzheimer's disease has been published (16).…”
Section: Expression Of Thyroid Nuclear Receptorsmentioning
confidence: 99%
“…Indeed, it has been shown in animals that retinoid, as well as thyroid, status modulates the plasticity of the adult brain (24,71) and that their age-associated alteration induces cognitive impairment (72). Moreover, high serum TSH level has been associated with depression in the elderly (73) and hypothyroidism is well known to induce cognitive impairment and dementia (74,75). The role of retinoids in brain aging seems of primary importance itself, in that evidence for defective retinoid transport and function in late-onset Alzheimer's disease has been published (16).…”
Section: Expression Of Thyroid Nuclear Receptorsmentioning
confidence: 99%
“…Although none of the patients had clinical somatic symptoms and signs of hypothyroidism, it is possible that their cognitive impairment was caused only by SCH. Cognitive impairment associated with SCH is defined as an improvement of cognitive performance after thyroid hormone replacement [5]. Of the 11 patients, however, 5 showed no improvement after thyroid hormone therapy, and the assessments of all patients were compatible with the NINCDS-ADRDA criteria for probable AD.…”
Section: Discussionmentioning
confidence: 99%
“…SCH, defined as a normal thyroid hormone level in the presence of a high thyroid-stimulating hormone (TSH) level [4], is relatively common in elderly people. Previous clinical studies have demonstrated that patients with SCH exhibit cognitive impairment, such as memory loss, or verbal fluency impairment [4,5,6]. Although demented patients with SCH are commonly encountered in daily clinical practice, there is less objective evidence supporting the effect of SCH on brain function in patients with Alzheimer's disease (AD).…”
Section: Introductionmentioning
confidence: 99%
“…Diversos trabalhos têm mostrado melhora do desempenho cognitivo com o tratamento, porém sem consenso definido na literatura (10,11,14,17,18). Contudo, caso seja evidenciada a potencialidade do tratamento nesses casos, a subsequente melhora da qualidade de vida deve ser analisada para se avaliar uma indicação formal do uso da levotiroxina em pacientes com HS.…”
Section: Discussionunclassified